2006
DOI: 10.1002/ijc.21955
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the European and North American studies on HPV testing in primary cervical cancer screening

Abstract: Several studies suggest that HPV testing is more sensitive than cytology in primary cervical screening. These studies had different designs and were reported in different ways. Individual patient data were collected for all European and North American studies in which cytology was routinely performed and HPV testing was included as an additional parallel test. More than 60,000 women were included. The sensitivity and specificity of HPV testing were compared with routine cytology, both overall and for ages <35,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
786
8
48

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 962 publications
(875 citation statements)
references
References 20 publications
33
786
8
48
Order By: Relevance
“…However, comparison of the HPV prevalence in opportunistically screened women aged 27 or 28 years to screening-eligible women aged 29 or 30 years did not show a trend shift in HPV prevalence (data not shown). Moreover, we observed an overall hrHPV prevalence of 21% in the age group 18 -24 years, which is consistent with the international literature (Winer et al, 2003;Manhart et al, 2006;Cuzick et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, comparison of the HPV prevalence in opportunistically screened women aged 27 or 28 years to screening-eligible women aged 29 or 30 years did not show a trend shift in HPV prevalence (data not shown). Moreover, we observed an overall hrHPV prevalence of 21% in the age group 18 -24 years, which is consistent with the international literature (Winer et al, 2003;Manhart et al, 2006;Cuzick et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…A related discussion concerns the choice of the primary screening instrument. Metaanalyses have shown that, HPV DNA testing has a higher sensitivity than cytology (Arbyn et al, 2006;Cuzick et al, 2006) and may be implemented in cervical screening in the future. In this study, we have shown that on removing HPV16/18 infections, the positive predictive values of HPV testing and cytology show similar decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Second, over 15 studies have consistently shown that the use of HPV DNA tests as the primary screening method is significantly more sensitive than cytology-based screening, either conventional or liquid based (International Agency for Research on Cancer, 2005;Cuzick et al, 2006a;Ronco et al, 2006;Mayrand et al, 2007). The summary gain in sensitivity is in the range of 25 -35%, and the reasons for it are clearly understood: (a) the presence of HPV DNA is a necessary prerequisite for cervical intraepithelial neoplasia (CIN) 2 þ ; (b) the sensitivity of HPV tests is consistently high (490%) across different laboratories, with an average level of sophistication in technology; (c) the detection of HPV DNA is independent of the limitations of any human eye observation, as it is the case with colposcopy, cytology and histology; and (d) HPV being often a field infection, the detection of the viral DNA is largely independent of the sampling ability to the point that selfsampling is able to detect HPV DNA at a similar level to that of the professionally collected cervical sample.…”
Section: Advances In Screeningmentioning
confidence: 99%
“…Since it does not directly test for cervical cancer but for HPV infection, a negative test result holds a high probability for the patient not to develop cervical cancer within 5-10 years following completion of the test, whereas a positive result only indicates the presence of an essential risk factor. 9 HPV infection is a very common condition in young women with prevalence over 25% in those aged younger than 30 years in Cameroon. 14 Studies carried out in other African countries found a PPV for HPV testing to be lower than 30%.…”
mentioning
confidence: 99%